A arte de aprender e ensinar: um estudo sobre a prática pedagógica dos egressos dos cursos de licenciatura em letras e matemática da URI/FW em sua relação com a formação docente acadêmica - Piovesan, Juliane Claudia (Universidade do Vale do Rio do Sinos, 2006)
The research, The Art of Learning and Teaching: a study about the Pedagogical Practice of the Graduate in the Graduation Courses of Language Arts and Matematics from the Regional Integrated University of Frederico Westphalen, in the State of Rio Grande do Sul, Brazil, in its relations to the Academic Formation of Educators which appeared from personal remarks and considerations of the researcher as a teacher in the Early Childhood Education. With that purpose one looks for to demonstrate how the art of learning and teaching was grasped by the graduate in the Graduation Courses of Language Arts and Matematics from the URI, of Frederico Westphalen and how that interferes in their pedagogical practices, that is to say, the aesthetic relation built during the teaching formation, while being a student-teacher, and the influences of that university formation process in practice at daily pedagogical work. The study is based on the theories of Freire and the written works by Assman, Arroyo, Cunha, Fernandes, Giroux,
Keywords: aprender; docência; ensinar; estética; prática pedagógica; formação docente; learning; aesthetics; pedagogical practice; teaching; teaching formation; Ciências Humanas